Improving carbon/carbon composites mechanical and thermal properties by the co‐carbonization of pre‐oxidized carbon fiber and pitch. Issue 13 (5th November 2021) - Li, Jie; Yang, Zefeng; Zhao, Yang; Li, Xiang; Wei, Wenfu; Li, Hao; Tu, Chuanjun; Chen, Qichen; Yin, Guofeng; Wu, Guangning
Abstract: The interfacial cracks generated during the high‐temperature carbonization process, caused by the mismatch of thermal shrinkage rate between the fiber and matrix, limit the huge application potential of C/C composites. In this study, pre‐oxidized carbon fiber (OPF) prepared from pitch, as a reinforcement, was introduced into the pitch‐based carbon matrix to realize the co‐carbonization of OPF and pitch. The results showed that the mechanical and thermal properties of the OPF‐reinforced C/C composites were significantly improved. The compressive strength and flexural strength were 136.97 and 46.71 MPa, respectively, both were about 2.5 times higher than those of pristine C/C composites. And OPF‐C/Cs had a carbon residual of about 30% at 800°C, which was 2.8, 4.4, and 2.1 times higher than that of Pristine‐C/Cs, CF‐C/Cs, and MCF‐C/Cs, respectively. The rough surface and abundant active sites of OPF could promote the growth of the graphite microcrystalline structure, resulting in an excellent fiber/matrix interface. Moreover, the adaptive expansion of OPF occurred during the co‐carbonization process with pitch, which inhibited the generation of cracks at the fiber/matrix interface. Owing to its excellent affinity with pitch, OPF is believed to have a wide range of promising applications in high‐performance C/C composites that require high‐temperature treatment. Abstract :